Calcium and Reactive Oxygen Species Signaling Interplays in Cardiac Physiology and Pathologies - Bianca De Nicolo; Erica Cataldi-Stagetti; Chiara Diquigiovanni; Elena Bonora (MDPI AG, 2023)
Mitochondria are key players in energy production, critical activity for the smooth functioning of energy-demanding organs such as the muscles, brain, and heart. Therefore, dysregulation or alterations in mitochondrial bioenergetics primarily perturb these organs. Within the cell, mitochondria are the major site of reactive oxygen species (ROS) production through the activity of different enzymes since it is one of the organelles with the major availability of oxygen. ROS can act as signaling molecules in a number of different pathways by modulating calcium (Ca2+) signaling. Interactions among ROS and calcium signaling can be considered bidirectional, with ROS regulating cellular Ca2+ signaling, whereas Ca2+ signaling is essential for ROS production. In particular, we will discuss how alterations in the crosstalk between ROS and Ca2+ can lead to mitochondrial bioenergetics dysfunctions and the consequent damage to tissues at high energy demand, such as the heart. Changes in Ca2+ can induce mitochondrial alterations associated with reduced ATP production and increased production of ROS. These changes in Ca2+ levels and ROS generation completely paralyze cardiac contractility. Thus, ROS can hinder the excitation-contraction coupling, inducing arrhythmias, hypertrophy, apoptosis, or necrosis of cardiac cells. These interplays in the cardiovascular system are the focus of this review.